Ethanol exposure during the third trimester equivalent does not affect GABA(A) or AMPA receptor-mediated spontaneous synaptic transmission in rat CA3 pyramidal neurons - Baculis, Brian Charles (J Negat Results Biomed, 2015)
BACKGROUND: Ethanol exposure during the rodent equivalent to the 3(rd) trimester of human pregnancy (i.e., first 1–2 weeks of neonatal life) has been shown to produce structural and functional alterations in the CA3 hippocampal sub-region, which is involved in associative memory. Synaptic plasticity mechanisms dependent on retrograde release of brain-derived neurotrophic factor (BDNF) driven by activation of L-type voltage-gated Ca(2+) channels (L-VGCCs) are thought to play a role in stabilization of both GABAergic and glutamatergic synapses in CA3 pyramidal neurons. We previously showed that ethanol exposure during the first week of life blocks BDNF/L-VGCC-dependent long-term potentiation of GABA(A) receptor-mediated synaptic transmission in these neurons. Here, we tested whether this effect is associated with lasting alterations in GABAergic and glutamatergic transmission. METHODS: Rats were exposed to air or ethanol for 3 h/day between postnatal days three and five in vapor inhalation chambers, a paradigm that produces peak serum ethanol levels near 0.3 g/dl. Whole-cell patch-clamp electrophysiological recordings of spontaneous inhibitory and excitatory postsynaptic currents (sIPSCs and sEPSCs, respectively) were obtained from CA3 pyramidal neurons in coronal brain slices prepared at postnatal days 13–17. RESULTS: Ethanol exposure did not significantly affect the frequency, amplitude, rise-time and half-width of either sIPSCs or sEPSCs. CONCLUSIONS: We show that an ethanol exposure paradigm known to inhibit synaptic plasticity mechanisms that may participate in the stabilization of GABAergic and glutamatergic synapses in CA3 pyramidal neurons does not produce lasting functional alterations in these synapses, suggesting that compensatory mechanisms restored the balance of excitatory and inhibitory synaptic transmission.